Analysis of the Benefits of Internships on Speaking Skills and Intercultural Competence by Japanese Language Education Study Program Students - Sondang Aldini Angelin Manurung; Diner, Lispridona (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Foreign language learning is highly prevalent in Indonesia, with Japanese being one of the most widely studied languages, largely due to strong bilateral cooperation between Indonesia and Japan. This collaboration has opened up employment opportunities and facilitated educational partnerships, particularly through internship programs between Japanese language study programs at universities and LPK Japan (Non-IM Japan). These placements motivate students to significantly improve their linguistic capabilities. This study aims to analyze the effect of internships in Japan on enhancing Japanese language students' speaking skills and intercultural competence. The research utilized a quantitative descriptive methodology with a questionnaire as the primary instrument. Sampling was conducted using purposive sampling, focusing on Japanese language program students who had participated in internships in Japan within the last 6 months to 1 year. The validity and reliability of the instrument were statistically confirmed using Pearson's correlation and Cronbach's Alpha, respectively, with 50 respondents. The results indicate that the internships provide significant advantages to the participants. Specifically, the findings show a positive correlation between the internship experience and both variables under study. Key benefits include an increase in student self-confidence and the ability to engage in effective cross-cultural exchange with host-country personnel. The study concludes that collaborative internship programs are highly effective in producing graduates who are professionally competent and interculturally aware.